Skin appendage abnormalities in hypothyroidism: understanding and management - Billewicz, Marta; Turek, Aleksandra; Makowska, Karolina; Lis, Laura; Marczyk, Aleksandra; Popiołek, Adam; Pietrzykowska, Julia (Journal of Education, Health and Sport, 2024)
Introduction and purpose Thyroid ailments are frequently encountered in medical practice, often intertwined with a variety of conditions that may or may not share common underlying factors. Among the organs profoundly influenced by these disorders is the skin, which manifests a diverse array of clinical presentations. However, the exact changes in the structure of skin appendages have not been well studied. Changes in hair structure or nail findings may be helpful in early diagnosis of thyroid disorders and therefore are important for dermatologist education. Hair loss can be a very uncomfortable and embarrassing ailment. Many diseases, nutritional deficiencies, stress and other factors can affect the hair condition and even induce its falling out. This review seeks to explore the numerous skin disorders arising directly or indirectly from thyroid irregularities, offering an updated understanding of the interplay between thyroid function and skin health. State of Knowledge It is well-established in scientific literature that thyroid gland disorders, particularly hypothyroidism, induce metabolic deceleration, influencing the inadequate nourishment of skin appendages, resulting in skin dryness and fragility. Patients commonly report pallor, cold intolerance, and deteriorating hair and nail quality. Conclusion We noticed strong correlation between hair loss and the autoimmune process during the dysfunction of thyroid. Euthyroidism plays an important role in hair cycle and any changes can disturb its proper development. In Hashimoto disease elevated levels of antibodies negatively influence hair cycle by excessively inducing telogen phase. Moreover, the blood vessels of the skin constrict disrupting the blood flow which affects hair follicles.